Blood pressure and occupational exposure to noise and lead (Pb): A cross-sectional study. (October 2016) - Rapisarda, Venerando; Ledda, Caterina; Ferrante, Margherita; Fiore, Maria; Cocuzza, Salvatore; Bracci, Massimo; Fenga, Concettina
Several studies have explored the hypothesis that low blood lead (PbB) and high noise levels may be associated with an increased risk of hypertension. To assess the possible relationship between occupational exposure to lead (Pb) and noise and elevated blood pressure, we studied 105 workers (age: 41.27 ± 6.25 years and length of employment: 4.12 ± 5.33 years) employed in a Pb battery recycling plant by measuring A-weighted equivalent sound level, PbB, δ-aminolevulinic acid dehydratase (ALAD) activity and zinc protoporphyrin (ZPP) levels and systolic and diastolic blood pressure (SBP and DBP). Results showed that occupational exposure to higher ambient Pb and noise levels was related to slightly increased SBP and DBP. PbB values correlated significantly with SBP and DBP, whereas noise levels correlated neither with SBP nor with DBP. Furthermore, workers exposed to higher ambient Pb had higher PbB and ZPP and showed more decreased ALAD activity. Blood pressure does not correlate with noise exposure but only with PbB concentration.